Implementasi ISAK 16: Aset Keuangan Atau Aset Tak Berwujud? - Sofiana Dewi; Made Dwi Cahaya Permana; Muhammad Iqbal; Amrie Firmansyah (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
This study aims to review the implementation and disclosure of concession rights in the company's financial statements in 4 (four) business sectors. In addition, this study reviews the extent to which service concessions are recognized as intangible or financial assets. This study uses a qualitative method with a content analysis technique. The data used in this content analysis are journals, theses, and internship reports with ten works of literature. This study concluded that the application of service concession accounting had been carried out following the provisions of ISAK 16 (2014), starting from the recognition, measurement, disclosure, and impact of its application. The company can disclose assets using financial and intangible assets according to an agreement between the government as the grantor and the private sector as the operator.